Comparison of the perceptions of managers and nursing staff toward performance appraisal - Tahere Moradi; Marzieh Adel Mehraban; Mahin Moeini (Iranian Journal of Nursing and Midwifery Research, 2017)
Background: Performance appraisal is an essential component of health care organizations for the improvement in quality of patients' care. Awareness of managers' and employees' perception of performance appraisal can lead to improved performance appraisal quality. The purpose of this study was to compare the perception of performance appraisal among managers and nursing staff of hospitals affiliated to Isfahan University of Medical Sciences, Isfahan, Iran. Materials and Methods: This descriptive-analytical and cross-sectional study was conducted among 75 managers and 313 nurses in 2014. The participants were selected through a two-stage quota-random sampling. Data were collected using two researcher-made questionnaires (nursing managers and nurses' questionnaires). Data were analyzed using descriptive and statistical tests using the Software Package for the Social Sciences software. Results: The mean score of managers' and nurses' perception of the current performance appraisal was 56.8 (14.2) and 51.4 (14.5), respectively. A significant difference was observed between managers' and nurses' perception of performance appraisal (P = 0.004). The participants' perception was examined in terms of performance appraisal method, the consequences of performance appraisal, and the necessity of performance appraisal. In general, perception of managers was more positive than employees. Conclusions: The evaluation of the perception of nurses revealed deficiencies in the process of performance appraisal. Moreover, managers had a more positive perception than employees toward the current pattern of performance appraisal. The results of this study can be effective on the decisions of authorities in this field.